The Settlement Principles and Effectiveness of Divorce by Mediation of Islamic Civil Perspective: A Critical Review of the Supreme Court Regulation - Abdullah Taufik (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Mediation of divorce is expected to be able to suppress the settlement of the case peacefully. In principle, based on the Elucidation of Law Number 1 of 19 74 concerning Marriage, marriage aims to form a happy and eternal family. Therefore, it is urgent to find mediation pillars in resolving divorce cases. To find the idea in response to these problems, there are three approaches: 1) laws and regulations, by examining them that relate to divorce settlement through mediation in religious courts; Supreme Court Regulation Numb. 1 of 2016, Civil Procedure Code. 2) from the view of experts/scholars, the conceptual approach is used to find ideas by building concepts and arguments according to the issues to be examined to find the efficiency in the implementation of mediation. 3) Philosophy, studying literacy related to the theme of the study to capture philosophical content in finding the pillars of mediation in the study of Islamic civil law. The findings in this study are the pillars of mediation whose relevance to divorce disputes should be stated: 1) Essence of Deliberation to reach an agreement. 2) The essence of mutual forgiveness is to end the dispute. 3) The essence of respecting the rights of others, of avoiding the nature of egoism. 4) The essence of justice is giving equal opportunity to speak to each other so that both parties have the same rights. The efficiency of the mediation implementation in the settlement of divorce can be achieved by mediating: 1) Regarding the care and education of children, 2) the cost of living of ex-wife, and 3) guarantee for the maintenance of the joint property after the termination of a marriage.